Intellectual Property's Territorial Framework and the Macro-Level Contradiction with Tax Policy - Frankel, Susy (Victoria University of Wellington Law Review, 2022)
Many large intellectual property owning firms have not paid "fair taxes" in the territories where they achieve sales and licences of their products. Rather, they tend to utilise regimes where they pay as little tax as possible. The international taxation system has allowed this to happen extensively. This is currently under challenge from some governments and the OECD. In this tribute to renowned tax scholar, John Prebble, the territorial nature of intellectual property is explained. Territoriality is a key organising principle of the existence of intellectual property rights, their exploitation and enforcement. At a high-level the territorial nature of intellectual property is not consistent with what happens to the profits of its exploitation, rather at a macro-level the frameworks of the international intellectual property regime and the international tax regimes are in contradiction.